2022
DOI: 10.3389/fpubh.2022.751768
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Geography of COVID-19 Case Fatality Rates in China: A Spatial Autoregressive Probit-Log Linear Hurdle Analysis

Abstract: This study employs a spatial autoregressive probit-log linear (SAP-Log) hurdle model to investigate the influencing factors on the probability of death and case fatality rate (CFR) of coronavirus disease 2019 (COVID-19) at the city level in China. The results demonstrate that the probability of death from COVID-19 and the CFR level are 2 different processes with different determinants. The number of confirmed cases and the number of doctors are closely associated with the death probability and CFR, and there e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…For example, Zhangjiakou City, one of the most severely affected cities, has not reported any death ( Figure 6 ). The deaths in the BTH area are concentrated in Beijing and Cangzhou because of medical resources shared between cities in the BTH area and the free medical treatment services provided for all infectors ( 44 ). A large number of discharged cases ( Figure 7 ) indicates that the treatment is effective, even though the proportion of the elderly population is relatively high; in fact, people aged 60 and above account for 25.9% of the cumulative confirmed cases in Beijing.…”
Section: Results Analysismentioning
confidence: 99%
“…For example, Zhangjiakou City, one of the most severely affected cities, has not reported any death ( Figure 6 ). The deaths in the BTH area are concentrated in Beijing and Cangzhou because of medical resources shared between cities in the BTH area and the free medical treatment services provided for all infectors ( 44 ). A large number of discharged cases ( Figure 7 ) indicates that the treatment is effective, even though the proportion of the elderly population is relatively high; in fact, people aged 60 and above account for 25.9% of the cumulative confirmed cases in Beijing.…”
Section: Results Analysismentioning
confidence: 99%
“…We use the STATA b1x2 package for decomposition analyses ( Gelbach, 2016 ). We have also performed zero-inflated Poisson and spatial analyses used in prior work ( Kathe & Wani, 2021 ; Yu et al, 2022 ) to examine whether the choice of OLS regressions biases our results. Results shown in Appendix Table A3 and Appendix Table A4 confirm that the results from all three approaches are substantively consistent.…”
Section: Methodsmentioning
confidence: 99%
“…There is also a growing body of literature investigating the links between geographical factors and the spread of COVID‐19 (Ascani et al., 2021; Desmet & Wacziarg, 2022; Giannone et al., 2022; Li & Ma, 2022; Liu et al., 2021; Yu et al., 2022). For example, Sun et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies examine the effect of medical factors on epidemic transmission and mortality rates (Bello-Chavolla et al, 2020;Chen et al, 2020;Kang, 2020;Sorouri et al, 2020). Yu et al (2022) demonstrate that the number of doctors and the number of confirmed cases have a significant influence on COVID-19 mortality rates in China, and medical knowledge and experience are very important for controlling the spread of COVID-19. To limit the spread of COVID-19, the Chinese government adopted innovative and advanced medical systems, such as mobile hospitals (方舱) and online medical services (Sun et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation